Tráfico de personas: una banalización más del mal moderno (2014)
This essay analyses one of the saddest and most lamentable problems of today, which is the trafficking of human beings in the world for sexual exploitation, forced labor, organ commercialization, and many other ends. Such practices, covered here by the rubric of human trafficking, are rejected by most of the countries; however, this is a profitable and growing business.